Penerapan Pembukuan UMKM Berbasis Template Excel Untuk Meningkatkan Akuntabilitas Keuangan Usaha Keripik Permata di Kabupaten Asahan - Cahyoginarti Cahyoginarti; Darmawati Darmawati; Ratna Ratna; Adhi Surya Harahap; Riswanto Riswanto (Lembaga Pengembangan Kinerja Dosen, 2025)
This community service program aims to improve the accountability and financial management capabilities of small businesses through the implementation of simple bookkeeping based on Excel templates at the Permata Chips MSME in Sentang Village, Asahan Regency. The main problems faced by partners were the lack of a transaction recording system, the mixing of business and personal finances, and the lack of financial reports that could be used to evaluate business performance. Through counseling, training, and technical assistance, this program succeeded in improving partners' financial literacy in preparing Excel-based Daily Cash Books, Profit and Loss Reports, Cash Flow Reports, and Balance Sheets. The results of the activity showed significant changes, where partners were able to record transactions systematically, document transaction evidence, and separate personal and business finances. The implementation of this bookkeeping became the basis for business decision-making and opened up opportunities for access to capital. Thus, this program contributed to improving small business accountability and is expected to be replicated in other MSMEs.